PWR/HDA9/ABI4 Complex Epigenetically Regulates ABA Dependent Drought Stress Tolerance in Arabidopsis - Khan, Irfan Ullah; Ali, Akhtar; Khan, Haris Ali; Baek, Dongwon; Park, Junghoon; Lim, Chae Jin; Zareen, Shah; Jan, Masood; Lee, Sang Yeol; Pardo, Jose M.; Kim, Woe Yeon; Yun, Dae-Jin (Frontiers in Plant Science, 2020)
Drought stress adversely affects plant growth and development and significantly reduces crop productivity and yields. The phytohormone abscisic acid (ABA) rapidly accumulates in response to drought stress and mediates the expression of stress-responsive genes that help the plant to survive dehydration. The protein POWERDRESS (PWR), which interacts with HISTONE DEACETYLASE 9 (HDA9), has been identified as a critical component regulating plant growth and development, flowering time, floral determinacy, and leaf senescence. However, the role and function of PWR and HDA9 in abiotic stress response had remained elusive. Here we report that a complex of PWR and HDA9 interacts with ABI4 and epigenetically regulates drought signaling in plants. T-DNA insertion mutants of PWR and HDA9 are insensitive to ABA and hypersensitive to dehydration. Furthermore, the expression of ABA-responsive genes (RD29A, RD29B, and COR15A) is also downregulated in pwr and hda9 mutants. Yeast two-hybrid assays showed that PWR and HDA9 interact with ABI4. Transcript levels of genes that are normally repressed by ABI4, such as CYP707A1, AOX1a and ACS4, are increased in pwr. More importantly, during dehydration stress, PWR and HDA9 regulate the acetylation status of the CYP707A1, which encodes a major enzyme of ABA catabolism. Taken together, our results indicate that PWR, in association with HDA9 and ABI4, regulates the chromatin modification of genes responsible for regulation of both the ABA-signaling and ABA-catabolism pathways in response to ABA and drought stress.